A chemically and mechanically stable dual-phase membrane with high oxygen permeation flux. Issue 45 (9th November 2020) - Nam, Gyeong Duk; Lee, Gahyeon; Choi, Soomin; Lee, Jinsil; Song, Sun-Ju; Joo, Jong Hoon
Abstract : This contribution details our comprehensive efforts to design a chemically and mechanically stable dual-phase membrane with a high oxygen permeation flux. Abstract : This contribution details our comprehensive efforts to design a chemically and mechanically stable dual-phase membrane with a high oxygen permeation flux. To enhance the mechanical and thermo-mechanical strength of a dual-phase membrane, GDC (Gd-doped ceria, Ce0.9 Gd0.1 O2− δ ) was added at 70 vol% to LSCF (La0.6 Sr0.4 Co0.2 Fe0.8 O3− δ ) in a dual-phase membrane within the electronic threshold for electronic conductivity. A highly active coating material (SrCo0.1 Fe0.8 Nb0.1 O3− δ, SCFN) was adopted in consideration of the relationship between the bulk diffusion ( D ) and surface exchange kinetics ( k ) of the dual-phase membrane, resulting in not only a high oxygen flux but also chemical stability in a CO2 atmosphere. The highest oxygen permeation flux obtained was 10.41 mL cm −2 min −1 at 1000 °C in the SCFN-coated dual-phase membrane; this is above the techno-economic target (5–10 mL cm −2 min −1 ) for the commercialization of oxygen transport membranes (OTMs) and comparable to that of BSCF (Ba0.5 Sr0.5 Co0.8 Fe0.2 O3− δ ) with a similar membrane thickness. The SCFN-coated dual-phase membrane also shows high CO2 -stability over 200 h and thermo-mechanical stability under rapid thermal cycling (20 °C min −1 ), which cannot be accomplished in single-phase membranes.